Improvement of reproducibility of macular volume measurements using the Heidelberg retinal tomograph. Issue 10 (1st October 2000) - Ang, A; Tong, L; Vernon, S A
Abstract : AIMS: To develop a more reproducible method of macular volumetric analysis in order to facilitate serial monitoring of changes in retinal oedema with time. METHODS: The Heidelberg retinal tomography (HRT) machine was used to scan the macula of 20 normal subjects and 40 diabetics with macular oedema. The volume above reference plane (VARP) within a 2 mm diameter and 3 mm diameter circle was measured twice in each eye. The position of the circle to be measured was carefully defined relative to major retinal vessels. As a modification to the previously published technique, fluctuation of the height of the contour line relative to the focal plane of the eye is compensated for by an adjustment of the reference plane. The position of the circle was controlled relative to major retinal vessels using an acetate. The reproducibility of VARP measurement was assessed by three variables—the standard error of the difference on two isolated VARP measurements, the standard error of the difference between the average of three readings on two different occasions, as well as the coefficient of variation (COV). RESULTS: Both the 2 mm and 3 mm circles showed good reproducibility in VARP measurements. In normal subjects, the COV of VARP for 2 mm circles and 3 mm circles were 13% and 12% respectively. In patients with macular oedema, the COV of VARP for 2 mm circles and 3 mm circles were 9% and 11% respectively. CONCLUSION: The modification of VARP measurements between scans of the same eye has improved the COV from 31% to 9% in eyes with diabetic macular oedema.